2019
DOI: 10.1183/13993003.02040-2018
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial pressure at rest and during exercise in chronic mountain sickness: a meta-analysis

Abstract: Up to 10% of the more than 140 million high-altitude dwellers worldwide suffer from chronic mountain sickness (CMS). Patients suffering from this debilitating problem often display increased pulmonary arterial pressure (PAP), which may contribute to exercise intolerance and right heart failure. However, there is little information on the usual PAP in these patients.We systematically reviewed and meta-analysed all data published in English or Spanish until June 2018 on echocardiographic estimations of PAP at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
1
19
1
3
Order By: Relevance
“…In contrast to early studies, a recent meta-analysis revealed that resting PAP in patients with chronic mountain sickness is only slightly higher compared to apparently healthy high altitude dwellers [278]. Nevertheless, in chronic mountain sickness patients, PAP is significantly more accentuated during even mild exercise associated with daily activity [278,279].…”
Section: Erythrocytosismentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to early studies, a recent meta-analysis revealed that resting PAP in patients with chronic mountain sickness is only slightly higher compared to apparently healthy high altitude dwellers [278]. Nevertheless, in chronic mountain sickness patients, PAP is significantly more accentuated during even mild exercise associated with daily activity [278,279].…”
Section: Erythrocytosismentioning
confidence: 81%
“…Interestingly, calculations of PAP values in high altitude dwellers, taking into account the hematocrit, revealed that higher values in Andeans are due to higher hematocrit levels compared to Tibetans [277]. In contrast to early studies, a recent meta-analysis revealed that resting PAP in patients with chronic mountain sickness is only slightly higher compared to apparently healthy high altitude dwellers [278]. Nevertheless, in chronic mountain sickness patients, PAP is significantly more accentuated during even mild exercise associated with daily activity [278,279].…”
Section: Erythrocytosismentioning
confidence: 87%
“…Soria et al. 22 concluded that HAPH is less common than previously expected at rest but frequent during daily activities. 22,23 However, according to Naeije, 23 this provocative finding must be reconciled with further analysis and validation.…”
Section: Epidemiology Of Hape and Haphmentioning
confidence: 94%
“…12 Interestingly, two recent publications raised some doubts about the actual prevalence of a pathological mean systolic PAP for defining HAPH at rest in individuals with or without CMS; a systematic review performed by Soria et al 22 investigated mostly healthy male Andeans (Aymaras and Quechuas) who were high-altitude residents with CMS using mean systolic PAP, and posteriorly in the editorial by Naeije, 23 he recalculated the mPAP. Soria et al 22 concluded that HAPH is less common than previously expected at rest but frequent during daily activities. 22,23 However, according to Naeije, 23 this provocative finding must be reconciled with further analysis and validation.…”
Section: High-altitude Pulmonary Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation